(untitled) (Journal of Parents and Teachers, 2017)
Mr. Morris Lessmore the protagonist lived in New Orleans surrounded by books. One day, while he was writing his story on a hotel balcony, he was moved by a strong hurricane to a desolated place far away from the city. While he was sadly walking and disoriented with his empty mind and without energy to write, he looked up and discovered a young girl guided by a lot of books which immensely flew to a place full of color and happiness. Morris wished that the same thing would happen to his book. Mr. Lessmore came across one of the books and invited it to follow him. They arrived to a house full of books, in which they could fulfill their anxieties to read and write with lots of imagination. There this person appeared until the end of his days enjoying and recreating a world full of unforgettable experiences.